2018
DOI: 10.1080/23761407.2018.1455616
|View full text |Cite
|
Sign up to set email alerts
|

STARS experiential group intervention: a complex trauma treatment approach for survivors of human trafficking

Abstract: This is the abstract that was submitted online with the paper: Despite the fact that many survivors of human trafficking have experienced complex trauma, there are no established interventions designed to specifically address these impacts. Leaders in the field of complex trauma have advocated for the need for somatic approaches to intervention. This paper presents STARS Experiential Group treatment, the first structured bodybased group intervention that has been designed to address complex trauma in survivors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(80 citation statements)
references
References 53 publications
0
80
0
Order By: Relevance
“…McMullen et al (2013) andO'Callaghan et al (2013) account for this by referring to the stigma former child soldiers can experience on return to their communities. The remaining three papers focussed on adolescent and adult survivors of sex trafficking (Hopper et al, 2018;Robjant et al, 2017) and child survivors of Restavek (Wang et al 2016). Wang et al (2016) identify that Restavek is a form a modern-day child slavery in Haiti.…”
Section: Study Design and Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…McMullen et al (2013) andO'Callaghan et al (2013) account for this by referring to the stigma former child soldiers can experience on return to their communities. The remaining three papers focussed on adolescent and adult survivors of sex trafficking (Hopper et al, 2018;Robjant et al, 2017) and child survivors of Restavek (Wang et al 2016). Wang et al (2016) identify that Restavek is a form a modern-day child slavery in Haiti.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…All nine studies reported the gender of the participants and 59.9% (319/532) were female. Two studies (Hermenau et al, 2013;McMullen et al, 2013) focussed on a male only sample and four were female only (Hopper et al, 2018;O'Callaghan et al, 2013;Robjant et al, 2017;Robjant et al, 2019). Whilst all the studies reported an age range, only five reported a mean age.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Mindfulness is a contemplative tradition of Buddhist origin, often defined as the ‘state of being attentive to and aware of what is taking place in the present’ (Brown and Ryan, 2003: 822). There are many forms of mindfulness practice, and Company A elects to start its practice with a short progressive muscle relaxation and body awareness exercise, recognizing that survivors often experience psychosomatic symptoms, impaired body awareness, and mind–body dissociation (Farb et al, 2015; Hoppera et al, 2018). The remaining time is spent prompting employees to maintain focus on their controlled breathing.…”
Section: Approach To Core Skills Developmentmentioning
confidence: 99%
“…There is other evidence that suggests abused women with higher levels of social support report better mental and physical health (Coker et al, 2002; Sherbourne, Meredith, Rogers, & Ware, 1992). And one qualitative study among trafficking survivors found experiential, somatically oriented group treatment showed promise (Hopper, Azar, Bhattacharyya, Malebranche, & Brennan, 2018). Group therapy provides social support in a structured way and empowers survivors to connect with resiliency within themselves and others.…”
Section: Discussionmentioning
confidence: 99%